Abandoned housing projects, legal risks and Islamic finance legal documentation - Mohd Yusof, Syarah Syahira; Oseni, Umar Aimhanosi; Hassan, Rusni (International Islamic University Malaysia, 2016)
This paper examines the role of effective legal documentation in mitigating the legal risks associated with abandoned housing projects in Malaysia. Specific attention is given to aspects relating to financial consumer protection, construction and interpretation of default clauses, and dispute management strategies, which seek to protect the interest of parties to the bundled agreements. Through conceptual analysis of relevant literature, legal documentary analysis, and unstructured interviews, this study adopts a qualitative legal research method to achieve its objective of ensuring legal risks associated with Islamic home financing are mitigated and financial consumers are adequately protected. Available legal remedies for the purchasers in the event of an abandoned housing project must be clearly included in the clauses relating to default in the Master agreement and financial guarantees, and effective dispute management processes should be considered to mitigate the triad of risks associated with abandoned housing projects – shariʿah, legal and reputational risks. This study provides a starting-point for further research on legal risks associated with abandoned housing projects, which seek to provide some minimum requirements for legal documentation in Islamic home financing. Legal documentation remains the bedrock of commercial dealings, and as such, it must be well crafted to avoid future disputes on contractual terms. Though previous studies have focused on the prevalence and the economic and financial impacts of abandoned housing projects, this is one of the earliest attempts to explore the legal risks associated with such projects with particular reference to legal documentation.